# Let P = 2x2 + 3x - 1 and Q = -3x2 + 4x - 1, then calculate P + Q and calculate P - Q.

### 3 Answers | Add Yours

p= 2x^2 + 3x - 1

Q = -3x^2 + 4x -1

Firt we will add P and Q:

P + Q = (2x^2 + 3x -1) + (-3x^2 + 4x -1)

We will combine like terms:

==> P + Q = 2x^2 - 3x^2 + 3x + 4x -1 -1

= -x^2 + 7x - 2

**==> P + Q = -x^2 + 7x - 2**

** **

Now for P - Q:

p - Q = (2x^2 + 3x -1) - (-3x^2 + 4x -1)

= 2x^2 + 3x -1 + 3x^2 - 4x + 1

Now combine like terms:

==> P - Q = 2x^2 + 3x^2 + 3x - 4x -1 + 1

= 5x^2 - x

**==> P - Q = 5x^2 - x**

P= 2x^2+3x-1 . Q = -3x^2+4x-1

Therefore P+Q = (2x^2+3x-1) +(-3x^2+4x+1)

We add like terms.

P+Q = (2x^2-3x^2)+(3x+4x)+(-1+1)

P+Q = -x^2 +7x+0

P+Q = -x^2+7x

2)

P-Q = (2x^2+3x-1)- (-3x^2+4x+1)

P-Q = 2x^2 +3x-1 -(-3x^2) -(4x) -(1)

P-Q = 2x^2+3x-1 +3x^2-4x-1

We collect similar terms.

P-Q = (2x^2+3x^2) +(3x-4x) +(-1-1)

P-Q = 5x^2-x -2

We have P = 2x^2 + 3x - 1 and Q = -3x^2 + 4x - 1

Now we have to calculate P + Q and P - Q.

P + Q

= 2x^2 + 3x - 1 + -3x^2 + 4x - 1

= -x^2 + 7x -2

P - Q

= 2x^2 + 3x - 1- ( -3x^2 + 4x - 1)

= 2x^2 + 3x - 1 + 3x^2 - 4x + 1

= 5x^2 - x

**Therefore P+Q = -x^2 + 7x -2 and P - Q = 5x^2 - x**